Corrosion-resistant aerial cable and production process thereof

By coating the composite coating on the outer sheath surface of the overhead cable, the ferrocene structure in carboxylated graphene and grafted cyclodextrin is solved, and the corrosion resistance and flame retardant problems of overhead cables are achieved, achieving longer use Lifespan and better fire protection.

CN119153160AInactive Publication Date: 2024-12-17ZHONGSHENG HONGTONG ELECTRIC POWER TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411167210.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing overhead cables are susceptible to atmospheric acid and alkali corrosion outdoors, resulting in wire corrosion and increased resistance, and the flame retardant capacity of the outer sheath layer is limited, which cannot meet market demand.

Method used

The surface of the overhead cable outer sheath is coated with a composite coating, using polyurethane coating as the matrix, and adding composite filler, which is made of carboxylated graphene, grafted cyclodextrin and ferrocene intermediates, forming a phosphate and sub- The coating of amine structure extends the reaction path of corrosive media and provides fire resistance.

Benefits of technology

It significantly improves the corrosion resistance and flame retardant properties of overhead cables, extends the service life, and provides fire protection in the case of fire to reduce the damage to the cables by fire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005008204500000091
    Figure BDA0005008204500000091
Patent Text Reader

Abstract

The invention relates to the field of aerial cables, in particular to a corrosion-resistant aerial cable and a production process thereof, the surface of an outer sheath of the aerial cable is coated with a composite coating, so that the problem that an existing aerial cable is insufficient in corrosion resistance is solved, and meanwhile the aerial cable has good flame retardance. A polyurethane coating used by the composite coating is prepared from the following raw materials in parts by weight: 40 to 50 parts of polyurethane resin, 4 to 6 parts of composite filler, 6 to 8 parts of polysiloxane emulsion, 10 to 15 parts of water, 0.8 to 1 part of antioxidant and 1 to 2 parts of thickening agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of overhead cables, and in particular to a corrosion-resistant overhead cable and a production process thereof. Background Art

[0002] Overhead cables have good insulation properties, electrical properties and mechanical strength. Taking into account safety, reliability, economy, easy maintenance and other factors, they are deeply loved by people. They have been widely used in 10kv distribution lines in urban and rural power grids and 35kv and below overhead power lines. Currently, common overhead cables usually include conductors, semi-conductive shielding layers and outer sheath layers.

[0003] However, overhead cables are usually exposed outdoors and are extremely susceptible to atmospheric acid and alkali corrosion. The corrosive medium penetrates into the interior of the cable, causing corrosion of the cable conductor, reducing the wire diameter of the conductor, and then increasing the resistance of the conductor and reducing the conductivity, thereby affecting the service life of the cable. In addition, since the outer sheath layer is mostly a polymer structure, its flame retardant ability is very limited and cannot meet the increasing market demand. Summary of the invention

[0004] The purpose of the present invention is to provide a corrosion-resistant overhead cable and a production process thereof, which solves the problem of insufficient corrosion resistance of the existing overhead cables and at the same time enables the cables to have good flame retardant properties.

[0005] The purpose of the present invention can be achieved by the following technical scheme: A corrosion-resistant overhead cable is prepared by the following steps: a polyurethane coating is applied to the surface of the overhead cable to form a composite coating, the thickness of the composite coating is controlled to be 50 μm, and then cured at a temperature of 70° C. for 8-10 hours to prepare a corrosion-resistant overhead cable;

[0006] The polyurethane coating is prepared by the following steps: weighing the following raw materials in parts by weight: 40-50 parts of polyurethane resin, 4-6 parts of composite filler, 6-8 parts of polysiloxane emulsion, 10-15 parts of water, 0.8-1 part of antioxidant and 1-2 parts of thickener, mixing the polyurethane resin, composite filler, polysiloxane emulsion, water, antioxidant and thickener to prepare the polyurethane coating;

[0007] The composite filler is prepared by the following steps:

[0008] Step A1: ferrocene and ether are mixed, and at a stirring rate of 120-150 rpm and room temperature, hexadecyltrimethylammonium bromide and 4-nitrobenzenediazonium chloride hydrochloric acid solution are added, and the reaction is carried out for 4-5 hours to obtain intermediate 1; intermediate 1, concentrated hydrochloric acid and ethanol are mixed, and at a stirring rate of 120-150 rpm and a temperature of 45° C., tin particles are added, and the reaction is carried out for 48 hours to obtain intermediate 2;

[0009] The mass concentration of 4-nitrobenzenediazonium chloride hydrochloric acid solution is 30%, the pH value is 5, the amount ratio of ferrocene, hexadecyltrimethylammonium bromide and 4-nitrobenzenediazonium chloride hydrochloric acid solution is 0.02-0.03 mol: 0.5-0.6 g: 18-20 mL, the mass fraction of concentrated hydrochloric acid is 38%, and the amount ratio of intermediate 1, concentrated hydrochloric acid, ethanol and tin particles is 0.015-0.02 mol: 70-80 mL: 120 mL: 13-14 g;

[0010] During the reaction, under acidic conditions and the action of hexadecyltrimethylammonium bromide, ferrocene and 4-nitrobenzenediazonium chloride undergo an arylation reaction to introduce a nitrophenyl group to obtain intermediate 1. The nitro group in intermediate 1 is then reduced under the action of concentrated hydrochloric acid and tin to form an amino group to obtain intermediate 2.

[0011] Step A2: p-Hydroxymethylbenzaldehyde, intermediate 2 and hydrochloric acid solution are mixed, and the mixture is reacted for 1-2 hours at a stirring rate of 120-150 rpm and a temperature of room temperature to obtain intermediate 3. Intermediate 3, triphenylphosphine, p-hydroxyanisole and acetone are stirred at a stirring rate of 200-300 rpm and a temperature of 50° C., and pyrophosphoric acid is added, and the mixture is reacted for 24 hours to obtain intermediate 4;

[0012] The mass concentration of the hydrochloric acid solution is 10%, the amount ratio of p-hydroxymethylbenzaldehyde, intermediate 2 and hydrochloric acid solution is 0.01-0.012 mol: 0.01-0.012 mol: 80-100 mL, and the amount ratio of intermediate 3, pyrophosphoric acid, triphenylphosphine and p-hydroxyanisole is 0.01-0.011 mol: 0.08-0.1 mol: 0.5-0.6 g: 0.3-0.4 g;

[0013] During the reaction, the aldehyde group in p-hydroxymethylbenzaldehyde first reacts with the amino group in intermediate 2 to form an imine structure to obtain intermediate 3. Then, under the action of triphenylphosphine and p-hydroxyanisole, the hydroxymethyl group in intermediate 3 reacts with pyrophosphoric acid to introduce a phosphate group to obtain intermediate 4.

[0014] Step A3: Carboxylated graphene, mono(6-amino-6-deoxy)-β-cyclodextrin and N,N-dimethylformamide are mixed, stirred at a stirring rate of 120-150 rpm and a temperature of 60°C, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are added, and the reaction is carried out for 2-3 hours to obtain a precursor, and the precursor, intermediate 4 and N,N-dimethylformamide are mixed, ultrasonically dispersed for 20 minutes, and then stirred at a stirring rate of 50-60 rpm and room temperature for 4-6 hours to obtain a composite filler;

[0015] The amount ratio of carboxylated graphene, mono(6-amino-6-deoxy)-β-cyclodextrin, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide is 0.3-0.4g:0.8-1g:0.02g:0.015g, and the amount ratio of precursor, intermediate 4 and N,N-dimethylformamide is 0.3-0.4g:0.2-0.24g:80-100mL;

[0016] During the reaction, under the action of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide, the carboxyl group in the carboxylated graphene reacts with the amino group in mono(6-amino-6-deoxy)-β-cyclodextrin to form an amide group, and a cyclodextrin structure is introduced to obtain a precursor. The cyclodextrin structure in the precursor and the ferrocene structure in the intermediate 4 undergo host-guest inclusion complexation to obtain a composite filler.

[0017] Beneficial effects of the invention: The invention relates to the field of overhead cables, and specifically to a corrosion-resistant overhead cable and a production process thereof. By coating a composite coating on the surface of the outer sheath of the overhead cable, the problem of insufficient corrosion resistance of the existing overhead cable is solved, and at the same time, the cable has good flame retardant properties. The composite filler in the composite coating is prepared by using carboxylated graphene as a matrix, grafting cyclodextrin, and then introducing a ferrocene intermediate 4 through host-guest inclusion. When the coating is contacted by an external corrosive medium and water molecules, the intermediate 4 contains a phosphate structure and an imine structure, which can be well At the same time, since the carboxylated graphene matrix in the composite filler is a lamellar structure and is grafted with cyclodextrin, this structure can greatly extend the propagation path of the corrosive medium, so that the corrosive medium is reacted to the maximum extent, thereby avoiding further penetration of the corrosive medium; and in the event of a fire disaster, since the composite filler contains a large amount of nitrogen and phosphorus elements and ferrocene structure, the composite coating can form a fireproof layer on the surface of the outer sheath of the overhead cable to achieve a flame retardant effect, and the carboxylated graphene structure in the composite filler can conduct heat, thereby slowing down the damage to the cable caused by the fire. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Example 1 A corrosion-resistant overhead cable is prepared by the following steps: applying a polyurethane coating to the surface of a commercially available Huiyou overhead cable to form a composite coating, the thickness of the composite coating is controlled to be 50 μm, and then curing at a temperature of 70° C. for 8 hours to obtain a corrosion-resistant overhead cable;

[0020] The polyurethane coating is prepared by the following steps: weighing the following raw materials in parts by weight: 40 parts of commercially available 8280D polyurethane resin, 4 parts of composite fillers, 6 parts of commercially available Nanmu D100 polysiloxane emulsion, 10 parts of water, 0.8 parts of commercially available 1010 antioxidant and 1 part of commercially available UH-530 thickener, mixing the polyurethane resin, composite fillers, polysiloxane emulsion, water, antioxidant and thickener to prepare the polyurethane coating;

[0021] The composite filler is prepared by the following steps:

[0022] Step A1: ferrocene and ether were mixed, and hexadecyltrimethylammonium bromide and 4-nitrobenzenediazonium chloride hydrochloric acid solution were added under stirring at a rate of 120 rpm and room temperature, and the mixture was reacted for 4 hours to obtain intermediate 1; intermediate 1, concentrated hydrochloric acid and ethanol were mixed, and tin particles were added under stirring at a rate of 120 rpm and a temperature of 45° C., and the mixture was reacted for 48 hours to obtain intermediate 2;

[0023] The mass concentration of 4-nitrobenzenediazonium chloride hydrochloric acid solution is 30%, the pH value is 5, the amount ratio of ferrocene, hexadecyltrimethylammonium bromide and 4-nitrobenzenediazonium chloride hydrochloric acid solution is 0.02mol:0.5g:18mL, the mass fraction of concentrated hydrochloric acid is 38%, and the amount ratio of intermediate 1, concentrated hydrochloric acid, ethanol and tin particles is 0.015mol:70mL:120mL:13g;

[0024] Step A2: p-Hydroxymethylbenzaldehyde, intermediate 2 and hydrochloric acid solution were mixed, and the mixture was reacted for 1 h at a stirring rate of 120 rpm and a temperature of room temperature to obtain intermediate 3. Intermediate 3, triphenylphosphine, p-hydroxyanisole and acetone were stirred at a stirring rate of 200 rpm and a temperature of 50° C., and pyrophosphoric acid was added, and the mixture was reacted for 24 h to obtain intermediate 4;

[0025] The mass concentration of the hydrochloric acid solution is 10%, the amount ratio of p-hydroxymethylbenzaldehyde, intermediate 2 and hydrochloric acid solution is 0.01 mol: 0.01 mol: 80 mL, and the amount ratio of intermediate 3, pyrophosphoric acid, triphenylphosphine and p-hydroxyanisole is 0.01 mol: 0.08 mol: 0.5 g: 0.3 g;

[0026] Step A3: commercially available XF004 carboxylated graphene, mono(6-amino-6-deoxy)-β-cyclodextrin and N,N-dimethylformamide were mixed, stirred at a stirring rate of 120 rpm and a temperature of 60°C, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide were added, and the reaction was carried out for 2 hours to obtain a precursor, and the precursor, intermediate 4 and N,N-dimethylformamide were mixed, ultrasonically dispersed for 20 minutes, and then stirred at a stirring rate of 50 rpm and room temperature for 4 hours to obtain a composite filler;

[0027] The amount ratio of carboxylated graphene, mono(6-amino-6-deoxy)-β-cyclodextrin, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide is 0.3g:0.8g:0.02g:0.015g, and the amount ratio of precursor, intermediate 4 and N,N-dimethylformamide is 0.3g:0.2g:80mL.

[0028] Example 2 A corrosion-resistant overhead cable is prepared by the following steps: applying a polyurethane coating to the surface of a commercially available Huiyou overhead cable to form a composite coating, the thickness of the composite coating is controlled to be 50 μm, and then curing at a temperature of 70° C. for 10 hours to obtain a corrosion-resistant overhead cable;

[0029] The polyurethane coating is prepared by the following steps: weighing the following raw materials in parts by weight: 50 parts of commercially available 8280D polyurethane resin, 4 parts of composite filler, 8 parts of commercially available Nanmu D100 polysiloxane emulsion, 10 parts of water, 0.8 parts of commercially available 1010 antioxidant and 2 parts of commercially available UH-530 thickener, mixing the polyurethane resin, composite filler, polysiloxane emulsion, water, antioxidant and thickener to prepare the polyurethane coating;

[0030] The composite filler is prepared by the following steps:

[0031] Step A1: ferrocene and ether were mixed, and hexadecyltrimethylammonium bromide and 4-nitrobenzenediazonium chloride hydrochloric acid solution were added under stirring at a rate of 120 rpm and room temperature, and the mixture was reacted for 5 hours to obtain intermediate 1; intermediate 1, concentrated hydrochloric acid and ethanol were mixed, and tin particles were added under stirring at a rate of 120 rpm and a temperature of 45° C., and the mixture was reacted for 48 hours to obtain intermediate 2;

[0032] The mass concentration of 4-nitrobenzenediazonium chloride hydrochloric acid solution is 30%, the pH value is 5, the amount ratio of ferrocene, hexadecyltrimethylammonium bromide and 4-nitrobenzenediazonium chloride hydrochloric acid solution is 0.03mol:0.6g:18mL, the mass fraction of concentrated hydrochloric acid is 38%, and the amount ratio of intermediate 1, concentrated hydrochloric acid, ethanol and tin particles is 0.015mol:80mL:120mL:13g;

[0033] Step A2: p-Hydroxymethylbenzaldehyde, intermediate 2 and hydrochloric acid solution were mixed, and the mixture was reacted for 1 h at a stirring rate of 150 rpm and a temperature of room temperature to obtain intermediate 3. Intermediate 3, triphenylphosphine, p-hydroxyanisole and acetone were stirred at a stirring rate of 300 rpm and a temperature of 50° C., and pyrophosphoric acid was added, and the mixture was reacted for 24 h to obtain intermediate 4;

[0034] The mass concentration of the hydrochloric acid solution is 10%, the amount ratio of p-hydroxymethylbenzaldehyde, intermediate 2 and hydrochloric acid solution is 0.01 mol: 0.012 mol: 80 mL, and the amount ratio of intermediate 3, pyrophosphoric acid, triphenylphosphine and p-hydroxyanisole is 0.011 mol: 0.08 mol: 0.6 g: 0.3 g;

[0035] Step A3: commercially available XF004 carboxylated graphene, mono(6-amino-6-deoxy)-β-cyclodextrin and N,N-dimethylformamide were mixed, stirred at a stirring rate of 150 rpm and a temperature of 60°C, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide were added, and the reaction was carried out for 2 hours to obtain a precursor, and the precursor, intermediate 4 and N,N-dimethylformamide were mixed, ultrasonically dispersed for 20 minutes, and then stirred at a stirring rate of 60 rpm and room temperature for 4 hours to obtain a composite filler;

[0036] The amount ratio of carboxylated graphene, mono(6-amino-6-deoxy)-β-cyclodextrin, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide is 0.4g:0.8g:0.02g:0.015g, and the amount ratio of precursor, intermediate 4 and N,N-dimethylformamide is 0.4g:0.24g:80mL.

[0037] Example 3 A corrosion-resistant overhead cable is prepared by the following steps: applying a polyurethane coating to the surface of a commercially available Huiyou overhead cable to form a composite coating, the thickness of the composite coating is controlled to be 50 μm, and then curing at a temperature of 70° C. for 10 hours to obtain a corrosion-resistant overhead cable;

[0038] The polyurethane coating is prepared by the following steps: weighing the following raw materials in parts by weight: 50 parts of commercially available 8280D polyurethane resin, 6 parts of composite fillers, 8 parts of commercially available Nanmu D100 polysiloxane emulsion, 15 parts of water, 1 part of commercially available 1010 antioxidant and 2 parts of commercially available UH-530 thickener, mixing the polyurethane resin, composite fillers, polysiloxane emulsion, water, antioxidant and thickener to prepare a polyurethane coating;

[0039] The composite filler is prepared by the following steps:

[0040] Step A1: ferrocene and ether were mixed, and hexadecyltrimethylammonium bromide and 4-nitrobenzenediazonium chloride hydrochloric acid solution were added under stirring at a rate of 150 rpm and room temperature, and the mixture was reacted for 5 hours to obtain intermediate 1. Intermediate 1, concentrated hydrochloric acid and ethanol were mixed, and tin particles were added under stirring at a rate of 150 rpm and a temperature of 45° C., and the mixture was reacted for 48 hours to obtain intermediate 2.

[0041] The mass concentration of 4-nitrobenzenediazonium chloride hydrochloric acid solution is 30%, the pH value is 5, the amount ratio of ferrocene, hexadecyltrimethylammonium bromide and 4-nitrobenzenediazonium chloride hydrochloric acid solution is 0.03mol:0.6g:20mL, the mass fraction of concentrated hydrochloric acid is 38%, and the amount ratio of intermediate 1, concentrated hydrochloric acid, ethanol and tin particles is 0.02mol:80mL:120mL:14g;

[0042] Step A2: p-Hydroxymethylbenzaldehyde, intermediate 2 and hydrochloric acid solution were mixed, and the mixture was reacted for 2 h at a stirring rate of 150 rpm and a temperature of room temperature to obtain intermediate 3. Intermediate 3, triphenylphosphine, p-hydroxyanisole and acetone were stirred at a stirring rate of 300 rpm and a temperature of 50° C., and pyrophosphoric acid was added, and the mixture was reacted for 24 h to obtain intermediate 4;

[0043] The mass concentration of the hydrochloric acid solution is 10%, the amount ratio of p-hydroxymethylbenzaldehyde, intermediate 2 and hydrochloric acid solution is 0.012 mol: 0.012 mol: 100 mL, and the amount ratio of intermediate 3, pyrophosphoric acid, triphenylphosphine and p-hydroxyanisole is 0.011 mol: 0.01 mol: 0.6 g: 0.4 g;

[0044] Step A3: commercially available XF004 carboxylated graphene, mono(6-amino-6-deoxy)-β-cyclodextrin and N,N-dimethylformamide were mixed, stirred at a stirring rate of 150 rpm and a temperature of 60°C, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide were added, and the reaction was carried out for 3 hours to obtain a precursor, and the precursor, intermediate 4 and N,N-dimethylformamide were mixed, ultrasonically dispersed for 20 minutes, and then stirred at a stirring rate of 60 rpm and room temperature for 6 hours to obtain a composite filler;

[0045] The amount ratio of carboxylated graphene, mono(6-amino-6-deoxy)-β-cyclodextrin, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide is 0.4g:1g:0.02g:0.015g, and the amount ratio of precursor, intermediate 4 and N,N-dimethylformamide is 0.4g:0.24g:100mL.

[0046] Comparative Example 1 Compared with Example 3, this comparative example replaces the polyurethane coating in the preparation process of the corrosion-resistant overhead cable in Example 3 with the commercially available Yingdan polyurethane anti-corrosion coating, and the other steps are the same.

[0047] Comparative Example 2 Compared with Example 3, this comparative example is characterized in that the composite filler in the preparation process of the polyurethane coating in Example 3 is replaced by a precursor, and the other steps are the same.

[0048] Comparative Example 3 Compared with Example 3, this comparative example is characterized in that the intermediate 4 in the preparation process of the composite filler in Example 3 is replaced by ferrocene, and the other steps are the same.

[0049] Take Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 to prepare corrosion-resistant overhead cables, immerse the corrosion-resistant overhead cables in a 10% hydrochloric acid solution at a temperature of 60°C for 7d, calculate the surface damage area ratio, and evaluate the acid corrosion resistance thereof; immerse the corrosion-resistant overhead cables in a 10% sodium hydroxide solution at a temperature of 60°C for 7d, calculate the surface damage area ratio, and evaluate the alkali corrosion resistance thereof; take the coatings used in the composite coatings of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, and perform the limiting oxygen index test with reference to GB / T2406.1-2008. The test results are shown in Table 1 below:

[0050] Table 1 Test results

[0051]

[0052] It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, Comparative Example 1 replaces the polyurethane coating in the preparation process of the corrosion-resistant overhead cable in Example 3 with the commercially available Yingdan polyurethane anti-corrosion coating, indicating that the polyurethane coating prepared by the present invention has greatly improved anti-corrosion performance and flame retardancy compared with commercially available coatings. Comparative Example 2 replaces the composite filler in the preparation process of the polyurethane coating in Example 3 with a precursor. Due to the lack of ferrocene structure, phosphate structure and imine structure, its corrosion resistance and flame retardancy are greatly reduced. Comparative Example 3 replaces the intermediate 4 in the preparation process of the composite filler in Example 3 with ferrocene. Due to the lack of phosphate structure and imine structure, its corrosion resistance and flame retardancy are greatly reduced.

[0053] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0054] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a corrosion-resistant overhead cable, characterized in that: The method is prepared by the following steps: applying a polyurethane coating on the surface of an overhead cable to form a composite coating, wherein the thickness of the composite coating is controlled to be 50 μm, and then curing the composite coating at a temperature of 70° C. for 8-10 hours to obtain a corrosion-resistant overhead cable; The polyurethane coating is prepared by the following steps: weighing the following raw materials in parts by weight: 40-50 parts of polyurethane resin, 4-6 parts of composite fillers, 6-8 parts of polysiloxane emulsion, 0.8-1 part of antioxidant and 1-2 parts of thickener, mixing the polyurethane resin, composite filler, polysiloxane emulsion, water, antioxidant and thickener to prepare the polyurethane coating.

2. The method for preparing a corrosion-resistant overhead cable according to claim 1, characterized in that: The composite filler is prepared by the following steps: Step A1: ferrocene and ether are mixed, and at a stirring rate of 120-150 rpm and room temperature, hexadecyltrimethylammonium bromide and 4-nitrobenzenediazonium chloride hydrochloric acid solution are added, and the reaction is carried out for 4-5 hours to obtain intermediate 1; intermediate 1, concentrated hydrochloric acid and ethanol are mixed, and at a stirring rate of 120-150 rpm and a temperature of 45° C., tin particles are added, and the reaction is carried out for 48 hours to obtain intermediate 2; Step A2: p-Hydroxymethylbenzaldehyde, intermediate 2 and hydrochloric acid solution are mixed, and the mixture is reacted for 1-2 hours at a stirring rate of 120-150 rpm and a temperature of room temperature to obtain intermediate 3. Intermediate 3, triphenylphosphine, p-hydroxyanisole and acetone are stirred at a stirring rate of 200-300 rpm and a temperature of 50° C., and pyrophosphoric acid is added, and the mixture is reacted for 24 hours to obtain intermediate 4; Step A3: Carboxylated graphene, mono(6-amino-6-deoxy)-β-cyclodextrin and N,N-dimethylformamide are mixed, stirred at a stirring rate of 120-150 rpm and a temperature of 60°C, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are added, and the reaction is carried out for 2-3 hours to obtain a precursor, and the precursor, intermediate 4 and N,N-dimethylformamide are mixed, ultrasonically dispersed for 20 minutes, and then reacted at a stirring rate of 50-60 rpm and room temperature for 4-6 hours to obtain a composite filler.

3. The method for preparing a corrosion-resistant overhead cable according to claim 2, characterized in that: In step A1: the mass concentration of 4-nitrobenzenediazonium chloride hydrochloric acid solution is 30%, the pH value is 5, the amount ratio of ferrocene, hexadecyltrimethylammonium bromide and 4-nitrobenzenediazonium chloride hydrochloric acid solution is 0.02-0.03 mol: 0.5-0.6 g: 18-20 mL, the mass fraction of concentrated hydrochloric acid is 38%, and the amount ratio of intermediate 1, concentrated hydrochloric acid, ethanol and tin particles is 0.015-0.02 mol: 70-80 mL: 120 mL: 13-14 g.

4. The method for preparing a corrosion-resistant overhead cable according to claim 2, characterized in that: In step A2: the mass concentration of the hydrochloric acid solution is 10%, the amount ratio of p-hydroxymethylbenzaldehyde, intermediate 2 and hydrochloric acid solution is 0.01-0.012mol: 0.01-0.012mol: 80-100mL, and the amount ratio of intermediate 3, pyrophosphoric acid, triphenylphosphine and p-hydroxyanisole is 0.01-0.011mol: 0.08-0.1mol: 0.5-0.6g: 0.3-0.4g.

5. The method for preparing a corrosion-resistant overhead cable according to claim 2, characterized in that: In step A3: the amount ratio of carboxylated graphene, mono (6-amino-6-deoxy) -β-cyclodextrin, 1-ethyl-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide is 0.3-0.4g: 0.8-1g: 0.02g: 0.015g, and the amount ratio of precursor, intermediate 4 and N, N-dimethylformamide is 0.3-0.4g: 0.2-0.24g: 80-100mL.

6. A corrosion-resistant overhead cable, characterized in that: Prepared according to any one of the preparation methods described in claims 1-5.